2007
DOI: 10.1021/jf071953k
|View full text |Cite
|
Sign up to set email alerts
|

Antiproliferative and Apoptotic Effects of Chamomile Extract in Various Human Cancer Cells

Abstract: Chamomile (Matricaria chamomilla), a popular herb valued for centuries as a traditional medicine, has been used to treat various human ailments; however, its anticancer activity is unknown. We evaluated the anticancer properties of aqueous and methanolic extracts of chamomile against various human cancer cell lines. Exposure of chamomile extracts caused minimal growth inhibitory responses in normal cells, whereas a significant decrease in cell viability was observed in various human cancer cell lines. Chamomil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
119
0
2

Year Published

2010
2010
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 181 publications
(125 citation statements)
references
References 25 publications
4
119
0
2
Order By: Relevance
“…Cytotoxic action of marigold tea is highly selective to target cancer cells being similar to the effect of chamomile tea; however, marigold tea exhibits significantly stronger cytotoxic action against malignant cell lines in comparison to chamomile tea (Matic et al, 2013;Srivastava & Gupta, 2007). In recent years, different extracts of Chamomilla recutita have shown to suppress the growth of various human malignant cell lines, such as prostate, cervical, colon, and breast cancer as well as leukemia cells (Kogiannou et al, 2013;Matic et al, 2013;Srivastava & Gupta, 2007. Besides the extraction techniques many other factors may play role in the biological activity of chamomile, including climatic and seasonal changes, harvest time, and storage conditions, whereas the major bioactive compound possessing anticancer activity in chamomile extract might be apigenin (Srivastava & Gupta, 2009).…”
Section: Herbsmentioning
confidence: 98%
See 1 more Smart Citation
“…Cytotoxic action of marigold tea is highly selective to target cancer cells being similar to the effect of chamomile tea; however, marigold tea exhibits significantly stronger cytotoxic action against malignant cell lines in comparison to chamomile tea (Matic et al, 2013;Srivastava & Gupta, 2007). In recent years, different extracts of Chamomilla recutita have shown to suppress the growth of various human malignant cell lines, such as prostate, cervical, colon, and breast cancer as well as leukemia cells (Kogiannou et al, 2013;Matic et al, 2013;Srivastava & Gupta, 2007. Besides the extraction techniques many other factors may play role in the biological activity of chamomile, including climatic and seasonal changes, harvest time, and storage conditions, whereas the major bioactive compound possessing anticancer activity in chamomile extract might be apigenin (Srivastava & Gupta, 2009).…”
Section: Herbsmentioning
confidence: 98%
“…Triterpene glycosides isolated from marigold flowers exhibit the potent cytotoxic activity against human colon cancer, leukemia, and melanoma cells (Ukiya et al, 2006) and the flower extract can suppress the metastatic spread of melanoma cells to lung in mice (Preethi et al, 2010). Cytotoxic action of marigold tea is highly selective to target cancer cells being similar to the effect of chamomile tea; however, marigold tea exhibits significantly stronger cytotoxic action against malignant cell lines in comparison to chamomile tea (Matic et al, 2013;Srivastava & Gupta, 2007). In recent years, different extracts of Chamomilla recutita have shown to suppress the growth of various human malignant cell lines, such as prostate, cervical, colon, and breast cancer as well as leukemia cells (Kogiannou et al, 2013;Matic et al, 2013;Srivastava & Gupta, 2007.…”
Section: Herbsmentioning
confidence: 99%
“…2) as well as the significant elevation of the levels of caspase-3/7 (Fig. 3) in cells treated with the extract of the plant strongly suggested that the mechanism of cell death could be apoptosis (26). However in future studies, the use of techniques such as DNA fluorescence will allow us to definitely confirm this observation.…”
Section: Resultsmentioning
confidence: 86%
“…The antioxidant characteristics of chamomile are associated with reducing lipid oxidation (Guimarães et al, 2013;Rekka, Kourounakis, & Kourounakis, 1996) and may influence consequences of peroxidation such as atherosclerosis. Additionally, apigenin glucosides and alpha-bisbolol found in chamomile have shown potential in inducing apoptosis in cancer cells (Cavalieri et al, 2004;Kassi et al, 2004;Ogata-Ikeda, Seo, Kawanai, Hashimoto, & Oyama, 2011;Srivastava & Gupta, 2007). Few human studies (especially prospective studies and clinical trials) exist on longterm effects of chamomile on health outcomes.…”
Section: Health Benefits Of Chamomilementioning
confidence: 99%